Synthesis, Characterization, and Biological Evaluation of Tetrahydropyrimidines: Dual-Activity and Mechanism of Action - Emilija Milović; Nenad Janković; Jelena Petronijević; Nenad Joksimović; Marijana Kosanić; Tatjana Stanojković; Ivana Matić; Nađa Grozdanić; Olivera Klisurić; Srđan Stefanović (MDPI AG, 2022)
In this paper, the synthesis, characterization, and biological evaluation of the novel tetrahydropyrimidines-THPMs are described. THPMs are well-known for wide pharmacological activities such as antimicrobial, anticancer, antiviral, etc. This research includes obtained results of in vitro antimicrobial, anticancer, and α-glucosidase inhibitory activities of the eleven novel THPMs. An antibiotic assessment was done against five bacteria (two Gram-positive and three Gram-negative) and five fungi by determining the minimal inhibitory concentration (MIC), using the broth tube dilution method. The most active antibacterial compounds were 4a, 4b, and 4d, while the best antifungal activity was shown by 4e, 4f, and 4k. The lowest MIC value (0.20 mg/mL) was measured for 4e, 4f, and 4k against the Trichophyton mentagrophytes. Moreover, examining the α-glucosidase inhibitory activity revealed the compound 4g as the one with the best activity. The cytotoxic activity was performed on the tumor cell lines (HeLa, K562, and MDA-MB-231) and normal cells (MRC-5). The best antitumor activity was shown by compounds 4b and 4k against HeLa cell lines. The influence on cell cycle and mechanism of action of the most active compounds were examined too. Compound 4b had good antibacterial and anticancer activities, while 4k showed promising antifungal and anticancer activities.